Manure applications combined with chemical fertilizer improves soil functionality, microbial biomass and rice production in a paddy field. (26th February 2022) - Iqbal, Anas; Liang, He; McBride, Steven G.; Yuan, Pengli; Ali, Izhar; Zaman, Maid; Zeeshan, Muhammad; Khan, Rayyan; Akhtar, Kashif; Wei, Shanqing; Guo, Zixiong; Jiang, Ligeng
Abstract: The current farming system is highly reliant on synthetic fertilizers, which adversely affect soil quality, the environment, and crop production. Improving crop productivity on a sustainable basis is a challenging issue in the current agricultural system. To address this issue, we assumed that the combined use of manure and chemical fertilizers (CF) could improve rice ( Oryza sativa L.) grain yield and soil properties without the expense of the environment. Therefore, a 2‐yr field experiment was conducted to explore optimal fertilizer management strategies using a combination of CF and organic fertilizer in the form of cattle manure (CM) or poultry manure (PM). Manure was added at two levels and soil microbial biomass production, enzyme activities, nutrient content, as well as grain yield of rice were measured. The study consisted of six treatments: no N fertilizer control, 100% chemical fertilizer (Pos‐Con), 60% cattle manure + 40% chemical fertilizer (High‐CM), 30% cattle manure + 70% chemical fertilizer, 60% poultry manure + 40% chemical fertilizer, and 30% poultry manure + 70% chemical fertilizer. Results showed that the addition of manure significantly increased soil enzymatic activities such as soil invertase, acid phosphatase (POH), urease, catalase (CAT), β‐glucosidase, and cellulase as compared to sole CF application. Similarly, the combined fertilizers application led to significant increases in soil microbial biomass C (MBC), microbial biomass N (MBN), soil pH, soil organic C (SOC), total N, available N (AN), available P (AP), and rice yield. Average increases in soil MBC, MBN, SOC AN, and AP in the 0‐to‐20‐cm soil depth were 62.2, 54.5, 29.2, 17.4, and 19.8%, respectively, across the years in the High‐CM treatment compared with the Pos‐Con. In addition, the linear regression analysis showed that soil enzymatic activities were highly positively correlated with soil MBC and MBN. The principal component analysis and linear regression analyses showed that the increased soil enzyme activities and microbial biomass production played a key role in the higher grain yield of rice. Overall, the results of this study demonstrate that the combined use of synthetic fertilizer and organic fertilizer in paddy fields could be beneficial for the farmers in southern China by improving soil functionality and yield of rice on a sustainable basis. Core Ideas: Insight and basis are provided into N management in double rice‐cropping systems. Reduced N fertilization combined with manure improved rice grain yield and soil fertility. Sixty percent organic N replacement with inorganic N had the most significant effect on soil properties. Correlation analysis showed that the enhancements in soil biochemical traits played a crucial role in higher soil quality and rice yields.